In vitro antibacterial activity of selected medicinal plants traditionally used in Vietnam against human pathogenic bacteria. Issue 1 (December 2015) - Vu, Thuy; Kim, Hyungrok; Tran, Vu; Le Dang, Quang; Nguyen, Hoa; Kim, Hun; Kim, In; Choi, Gyung; Kim, Jin-Cheol
Abstract Background Medicinal plants are widely used for the treatment of different infectious diseases. Infectious diseases caused by bacteria have a large impact on public health. This study aimed to determine the in vitro antibacterial activity of the medicinal plants traditionally used in Vietnam against the bacterial strains associated with infectious diseases. Methods Methanol extracts of twelve Vietnamese medicinal plants were tested for their antibacterial activity against five bacterial species including Gram-positive bacteria (Bacillus cereus, Bacillus subtilis, andStaphylococcus aureus ) and Gram-negative bacteria (Escherichia coli andPseudomonas aeruginosa ) using the broth microdilution method. Results All the plant extracts showed antibacterial activity, especially against Gram-positive bacteria (Bacillus cereus, Bacillus subtilis, andStaphylococcus aureus ).Baeckea frutescens extract revealed a potent activity against the Gram-positive bacteria with the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of 62.5 μg/ml. High activity against all the three Gram-positive bacteria was also observed for the extracts ofCratoxylum formosum ssp.pruniflorum, Pogostemon cablin, andPedilanthus tithymaloides with MICs of 125, 125 and 250 μg/ml and MBCs of 125–250, 125–250 and 250–500 μg/ml, respectively. The extracts ofC. formosum ssp.pruniflorum andP. tithymaloides showed a broad-spectrum antibacterial activity against all the bacteria tested with the MICs of 125–2, 000 μg/ml. Conclusion This study indicates clear evidence supporting the traditional use of the plants in treating infectious diseases related to bacteria. In particular, these plant species showed moderate to high antibacterial activity against the Gram-positive bacteria tested.